Nitrogen‐Bridged Metallodiazaporphyrin Dimers: Synergistic Effects of Nitrogen Bridges and meso‐Nitrogen Atoms on Structure and Properties. Issue 7 (28th February 2017) - Kawamata, Masahiro; Sugai, Takuma; Minoura, Mao; Maruyama, Yasuhisa; Furukawa, Ko; Holstrom, Cole; Nemykin, Victor N.; Nakano, Haruyuki; Matano, Yoshihiro
Abstract: NH‐bridged and pyrazine‐fused metallodiazaporphyrin dimers have been prepared from nickel(II) and copper(II) complexes of 3‐amino‐5, 15‐diazaporphyrin by Pd‐catalyzed C−N cross‐coupling and oxidative dimerization reactions, respectively. The synergistic effects of the nitrogen bridges and meso ‐nitrogen atoms play major roles in enhancing the light‐harvesting properties and delocalization of an electron spin over the entire π‐skeletons of the metallodiazaporphyrin dimers. Abstract : Planar and twisted dimers of diazaporphyrin : NH‐bridged and pyrazine‐fused 5, 15‐diazaporphyrin dimers have been prepared from 3‐amino‐5, 15‐diazaporphyrins. The synergistic effects of the nitrogen bridges and meso ‐nitrogen atoms played major roles in enhancing the light‐harvesting properties and delocalization of an electron spin over the entire π‐skeletons of the diazaporphyrin dimers.